2001
DOI: 10.1001/archinte.161.21.2596
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Computer-Tailored Smoking Cessation Program

Abstract: The program was effective in increasing smoking cessation rates. Because it can reach a large number of smokers, this program can substantially contribute to disease prevention at a population level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
107
4
4

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(118 citation statements)
references
References 39 publications
3
107
4
4
Order By: Relevance
“…Overall, 30 studies 34,[36][37][38][39][40][42][43][44]46,48,49,53,[55][56][57][58]61,66,69,72,75,80,88,91,96,97,109,110 that randomised between 72 and 3627 participants and followed up between 3 and 30 months evaluated the effect of tailored printed materials. In the meta-analysis, computer-generated, tailored printed materials were effective in increasing smoking cessation compared with no intervention or generic self-help materials.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, 30 studies 34,[36][37][38][39][40][42][43][44]46,48,49,53,[55][56][57][58]61,66,69,72,75,80,88,91,96,97,109,110 that randomised between 72 and 3627 participants and followed up between 3 and 30 months evaluated the effect of tailored printed materials. In the meta-analysis, computer-generated, tailored printed materials were effective in increasing smoking cessation compared with no intervention or generic self-help materials.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Tailored printed materials also appear to be effective in studies in which the smokers were not ready to quit at the start of the study, but there was significant heterogeneity in effect estimates (I 2 = 85%, p < 0.001). Overall, only five studies 53,56,88,97,109 demonstrated a statistically significant increase in abstinence rates in the intervention groups compared with the control groups. Figure 21 shows the results of point prevalence abstinence measured at the last follow-up of each study.…”
Section: Comparisons and Findingsmentioning
confidence: 94%
See 1 more Smart Citation
“…Data were collected between September 2000 and June 2001. An invitation to fill the survey was sent by e-mail to 5000 smokers who participated in the 'Stop-tabac.ch' smoking cessation program (Etter and Perneger, 2001b). A link to the questionnaire was also posted on several pages of this site.…”
Section: Main Surveymentioning
confidence: 99%
“…49 Concerns of neuropsychiatric harms of varenicline and bupropion also exist, including changes in mood (including depression and mania), psychosis, hallucinations, paranoia, delusions, homicidal ideation, hostility, agitation, aggression, anxiety, and panic, as well as suicidal ideation, suicide attempt, and completed suicide. 50,51 With most trials excluding patients with a history of neuropsychiatric disease, neuropsychiatric adverse event data are limited. However, the recently completed the EAGLES (Evaluating Adverse Events in a Global Smoking Cessation Study) trial found no increase in neuropsychiatric adverse events among patients randomized to varenicline or bupropion relative to those randomized to nicotine patch or placebo.…”
mentioning
confidence: 99%